Law of cosines

From Math Images

(Difference between revisions)
Jump to: navigation, search
(example triangulation)
Line 35: Line 35:
==Example Triangulation==
==Example Triangulation==
Complete the triangle using the law of cosines.
Complete the triangle using the law of cosines.
 +
 +
 +
<math> c^{2} = a^{2} + b^{2} - 2ab \cos C </math>
[[Image:SAS triangle.jpg]]
[[Image:SAS triangle.jpg]]
To find the side length <math>c</math>,
To find the side length <math>c</math>,
 +
 +
 +
<math> c^{2} = 6^{2} + (6 \sqrt{2})^{2} -2 (6) (6 \sqrt{2}) \cos 45^\circ </math>
 +
 +
Simplify for
 +
 +
<math> c^{2} =36 + 36 (2) - 72 \sqrt{2}) \cos 45^\circ </math>
 +
 +
Since <math> \cos 45^\circ = \frac{1}{\sqrt{2}}</math>, substitution gives us
 +
 +
<math> c^{2} =36 + 36 (2) - 72 \sqrt{2} (\frac{1}{\sqrt{2}}) </math>
 +
 +
Simplify for
 +
 +
<math> c^{2} =36 + 72 - 72 </math>
 +
 +
 +
<math> c^{2} =36 </math>
 +
 +
Taking the square root of both sides gives us
 +
 +
<math> c =6 </math>
 +
 +
----
 +
 +
 +
Now we can orient the triangle differently to get get a new version of the law of cosines so we can find angle measure <math>B</math>,
 +
 +
 +
<math> b^{2} = a^{2} + c^{2} - 2ab \cos B </math>

Revision as of 10:54, 30 May 2011

The law of cosines is a formula that helps in triangulation when two or three side lengths of a triangle are known. The formula relates all three side lengths of a triangle to the cosine of a particular angle.

 c^{2} = a^{2} + b^{2} - 2ab \cos C

When to use it: SAS, SSS.

Proof

Let  \vartriangle ABC be oriented so that  C is at the origin, and  B is at the point (a,0).

Image:Law_of_cosines_proof.jpg

Distance Formula

 distance = \sqrt {(x_{2}-x_{1})^{2} + (y_{2}-y_{1})^{2}}

c is the distance from  A to  B.

Substituting the appropriate points into the distance formula gives us

 c = \sqrt {(a-b \cos C)^{2} + (0-b \sin C)^{2}}

Squaring the inner terms, we have

 c = \sqrt {(a^{2}-2ab \cos C+b^{2} \cos^{2} C) + (b^{2} \sin^{2} C)}

Since  \cos^{2} C +  \sin^{2} C = 1,

 c = \sqrt {(a^{2}+b^{2}-2ab \cos C+b^{2}}

Square both sides for

 c^{2} = (a^{2}+b^{2}-2ab \cos C+b^{2}

Example Triangulation

Complete the triangle using the law of cosines.


 c^{2} = a^{2} + b^{2} - 2ab \cos C

Image:SAS triangle.jpg

To find the side length c,


 c^{2} = 6^{2} + (6 \sqrt{2})^{2} -2 (6) (6 \sqrt{2}) \cos 45^\circ

Simplify for

 c^{2} =36 + 36 (2) - 72 \sqrt{2}) \cos 45^\circ

Since  \cos 45^\circ = \frac{1}{\sqrt{2}}, substitution gives us

 c^{2} =36 + 36 (2) - 72 \sqrt{2} (\frac{1}{\sqrt{2}})

Simplify for

 c^{2} =36 + 72 - 72


 c^{2} =36

Taking the square root of both sides gives us

 c =6



Now we can orient the triangle differently to get get a new version of the law of cosines so we can find angle measure B,


 b^{2} = a^{2} + c^{2} - 2ab \cos B

Personal tools